Developing a Sustainable Technical Work with Environmental Augmented Reality on Innovative Modul Training - Wahyuni, Dessy Seri; Ariadi, Gede; Agustini, Ketut; Mertayasa, I Nengah Eka (Universitas Negeri Semarang, 2023)
The present research aimed to reveal whether an augmented reality (AR) direction method would result in more rapid job accomplishment times, reduce mental workload, and have limited faults for simple duties in operational programming. This paper proposes a marker-based mobile AR application called SIPEMA-AR to improve the sustainable, innovative training module to provide interactive content in the form of work instructions for the water meter reading process in the context of a regional water company of workers’ training. Previous research on technical work which directly compared AR directions to conventional direction methods (e.g., paper) appeared which AR directions can increase technical work. However, this needed to be more accurate for modest duties in an operational setting. Applicants fulfilled modest technical tasks on the SIPEMA-AR application utilizing AR and paper command methods. The research results indicate that AR instruction has a significant influence on the time needed to do the task could be categorized as fast and the mental of workload could be categorized as low. Using AR instructions before paper instructions provides training that sustainably builds on paper instructions. The SIPEMA-AR application can be used as a support for modest tasks that focus on operational work. The SIPEMA-AR application can avoid problems that occur in operational work. This is because the time, effort, and funds needed in operational work can be minimized and provide maximum results.